Memahami Peran Lembaga Pembiayaan Syari’ah Dalam Meningkatkan Aksesibilitas Keuangan UMKM Pada Masa Pandemi Covid19 - Misbahul Ilham; Iswi Hariyani (Universitas Widya Gama Malang, 2020)
This paper aims to discuss the ability of Islamic financial institutions to accommodate micro and medium enterprises (UMKM) financing through the Financial Services Authority Regulation. The Covid19 pandemic that is currently happening has greatly affected the sustainability and inclusiveness of UMKM caused by large-scale social risks (PSBB). The result is the limited movement of people in one area, especially UMKM in reaching Islamic financial institution facilities. Financial Technology was one of the options during the Covid19 pandemic, but the Financial Services Authority Regulation Number 77 / POJK.01 / 2016 concerning Information Technology-Based Borrowing and Lending Services has not been able to accommodate shari'ah fintech as an option for shari'ah financing during the COVID-19 pandemic